(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
The electric and magnetic properties of matter play an important role in the fabrication of electronic chips. This encourages us to do this work. In this work, eight NaCl samples were prepared and crushed into different micro and nano sizes. Their nano sizes were examined using an X-ray diffraction technique, and their electrical and magnetic properties were examined using a visible and ultra violet spectrometer. The results obtained indicate that the electric conductivity, electric permittivity, and magnic permeability decrease for short wavelengths and increase for long wave lengths upon increasing the crush and nano sizes.